2016
DOI: 10.1007/s11136-016-1259-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of individuals born preterm: a systematic review of assessment approaches

Abstract: Agreement between parents and children about QoL in preterm individuals was lower in younger age groups compared with older age groups. The differences in QoL throughout the different age groups may have arisen because of developmental changes or differences in the source of information used (i.e., parent report or self-report). We recommend that QoL assessments in children born preterm should consider both parent report and self-report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 66 publications
1
25
0
7
Order By: Relevance
“…Our work does not confirm this at school age when the QoL levels are lower and concordant between the parents and their infant. Generally, even if the parents’ perceptions agree with their children’s regarding physical health, they diverge in the more subjective areas such as psychological and psychosocial domains 8. In children 8 to 12 years old, it is the psychosocial domain (self-esteem, relationship with friends, then school) 30.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work does not confirm this at school age when the QoL levels are lower and concordant between the parents and their infant. Generally, even if the parents’ perceptions agree with their children’s regarding physical health, they diverge in the more subjective areas such as psychological and psychosocial domains 8. In children 8 to 12 years old, it is the psychosocial domain (self-esteem, relationship with friends, then school) 30.…”
Section: Discussionmentioning
confidence: 99%
“…A preterm QoL meta-analysis in 20087 and 20168 selected 37 studies, 5 of which were school-aged children who were born very preterm (<32 GA). Only three EPT children’s studies have been undertaken (395 total children).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review focused on outcomes following neonatal cerebellar injury and found reduced cerebellar volumes were correlated with higher prevalence of behavioural abnormalities . Other findings included evidence of persistent corticospinal tract injury , and widespread reductions and disruptions in intrinsic and resting‐stage connectivity of networks . Reduced overall IQ scores and lower math abilities were also reported frequently.…”
Section: System/organ‐specific Outcomesmentioning
confidence: 99%
“…According to World Health Organization (WHO), a newborn with less than 37 weeks of gestation is to be considered premature, or preterm. 1 Scarce gestational age and low birth weight are the main factors closely related to neonatal complications and pathologies. Many anomalies involving the oral cavity are particularly frequent in such patients: among the most prevalent oral alterations, preterm children are suffering from dental caries, malocclusion, enamel hypoplasia and dental discolorations.…”
Section: Introductionmentioning
confidence: 99%